2022
DOI: 10.1088/2058-6272/ac6e34
|View full text |Cite
|
Sign up to set email alerts
|

Development of low power non-thermal plasma jet and optimization of operational parameters for treating dyes and emerging contaminants

Abstract: Non-thermal plasma has emerged as an effective treatment system against the latest class of highly recalcitrant and toxic environmental pollutants termed emerging contaminants (ECs). In the present work, a detailed experimental study is carried out to evaluate the efficacy of a non-thermal plasma jet with two dyes, Rd. B and Met. Blue, as model contaminants. The plasma jet provided a complete dye decoloration in 30 min with an applied voltage of 6.5 kVp−p •OH, having the highest oxidation potential, acts as th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…In this study, an increase in inactivation for both drugresistant Gram-negative bacillus (MDR E. coli) and Grampositive cocci (MDR S. aureus) was observed with an increase in CAP exposure time. This result is concordant with previous studies [22], [25], [26], [61]. The prolonged interaction of CAP species (Ar I, OH .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, an increase in inactivation for both drugresistant Gram-negative bacillus (MDR E. coli) and Grampositive cocci (MDR S. aureus) was observed with an increase in CAP exposure time. This result is concordant with previous studies [22], [25], [26], [61]. The prolonged interaction of CAP species (Ar I, OH .…”
Section: Discussionsupporting
confidence: 93%
“…The thermocouple probe tip was insulated and calibrated for the measurement of plume temperature. The details of the developed CAPJ system can be found elsewhere [22]. All the experiments in this study were performed at a fixed applied voltage of 6.5 kVp-p, 25 kHz frequency, and argon gas at a flow rate of 3 lpm.…”
Section: Methodsmentioning
confidence: 99%
“…ROS/RNS have therapeutic effects when administered to cells and tissues either directly from the plasma or by exposure to solutions that have already been plasma-treated. Optimization of the NTAPP treatment remained an active topic of research [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The copious of RONS, ions, electrons, and excited species integrates an antimicrobial nature to the discharge [17,[24][25][26][27][28][29]. The efficacy of CAP in removing the microbial load from nutrient culture media [24,[30][31][32][33][34] or liquid suspensions [24,31,[35][36][37] have been studied. Das et al [24] and Flynn et al [38] showed the efficacy of CAP jet on the inactivation of clinically isolated ESKAPE pathogens.…”
Section: Introductionmentioning
confidence: 99%